Language Feasibility in Indonesian Language Textbooks for Grade X Vocational High School (SMK/MAK) - Afriana Marisa; Memet Sudaryanto; Bivit Anggoro Prasetyo Nugroho (Transpublika Publisher, 2025)
Language is one of the important aspects in determining the feasibility of textbooks. This is because language quality determines the effectiveness of textbooks in delivering material. The use of inappropriate language can cause the learning process to become less optimal. As the main learning resource, textbooks need to present language that conforms to linguistic rules. This research aims to describe the language feasibility contained in Indonesian Language textbooks for SMK/MAK class X published by Ministry of Education, Culture, Research, and Technology (Kemendikbud) and Erlangga. The type of approach used is descriptive qualitative with content analysis research method. Meanwhile, the data collection techniques used are documentation and sampling, as well as conducting data analysis with an interactive model. The results of language feasibility research show that both textbooks obtained a very feasible category with a slight percentage difference. The Kemendikbud textbook received a percentage of 94%, while the Erlangga textbook showed a percentage of 92%. Overall, both textbooks show findings that are in accordance with the assessment indicators. Thus, this study is expented to be beneficial for teacher and students in using textbooks according to their needs. The findings may also contribute to the development of higher-quality textbooks in the future.